Pengalaman Keluarga Dalam Mencari Pengobatan Pada Gangguan Jiwa - Noorwahyu Trihidayati; Iman Permana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Seek treatment is a continuous process, where the symptoms of the disease suffered have increased and can gradually be seen, evaluated and finally treated through the initiation of specific interventions Early symptoms of mental disorders are not always seen by lay people, so the search for treatment for psychosis is sometimes sometimes delayed. Delays in seeking treatment will lead to worse results. The process of seeking treatment will be repeated until recovery goals are achieved. Objective: To find out family experiences in seeking treatment in patients with mental disorders. Methods: The method used in this review literature by analyzing several articles using data base at EBSCO, Science direct, Pupmed and Google scholar, then extraction using the keywords